Analysis of Differences in the Use of Verb Synonyms in Indonesian Language - Raviqa, Raviqa (ELS Journal on Interdisciplinary Studies in Humanities, 2020)
This study aims to analyze the differences in the use of verb synonyms in Indonesian language. Data are verbs and their synonym members, which are collected using observation and note-taking techniques. Data were analyzed using substitution and descriptive methods. The results showed that the distribution analysis provided two possible characteristics. The first possibility consisted of a number of verbs which have the possibility to distribute in parallel with all members of the synonym and the second possibility was the verbs that could not substitute one another (complementarily distributed) with all members of the synonym.